EFFECT OF CUTTING PARAMETER ON THE TOOL LIFE OF THE UNCOATED CARBIDE TOOL DURING TURNING USING MINIMUM QUANTITY LUBRICATION (MQL) - Sulaiman, M.A.; Asiyah, M.S.; Shahmi, R.; Mohamad, E.; Mohamad, N.A.; Md Ali, M.A.; Yuniawan, D.; Ito, T. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Titanium alloy is one of the advance material that has unique characteristics; difficult to cut and higher chemical reactivity. However, this material always receive many demands from the aerospace, medical and automotive industries. During turning of titanium alloy, the issues that always discussed are rapid tool wear and high cutting temperature. During the time the rapid tool wear take places, it automatically influence the life of the cutting tool. This studies focused on the effect of minimum quality lubrication (MQL) technique during turning titanium alloy Ti-6Al-4V ELI on the tool life of uncoated carbide. From the experiment, the longest tool life that recorded is 54.22 minutes obtained at the minimum cutting parameters while the shortest tool life is 1.50 minutes obtained at the maximum combinations of cutting parameters.